Assessment of social psychological determinants of satisfaction with childbirth in a cross-national perspective - Bracke Piet; Christiaens Wendy (BMC, 2007)
Abstract Background The fulfilment of expectations, labour pain, personal control and self-efficacy determine the postpartum evaluation of birth. However, researchers have seldom considered the multiple determinants in one analysis. To explore to what extent the results can be generalised between countries, we analyse data of Belgian and Dutch women. Although Belgium and the Netherlands share the same language, geography and political system and have a common history, their health care systems diverge. The Belgian maternity care system corresponds to the ideal type of the medical model, whereas the Dutch system approaches the midwifery model. In this paper we examine multiple determinants, the fulfilment of expectations, labour pain, personal control and self-efficacy, for their association with satisfaction with childbirth in a cross-national perspective. Methods Two questionnaires were filled out by 605 women, one at 30 weeks of pregnancy and one within the first 2 weeks after childbirth either at home or in a hospital. Of these, 560 questionnaires were usable for analysis. Women were invited to participate in the study by independent midwives and obstetricians during antenatal visits in 2004-2005. Satisfaction with childbirth was measured by the Mackey Satisfaction with Childbirth Rating Scale, which takes into account the multidimensional nature of the concept. Labour pain was rated retrospectively using Visual Analogue Scales. Personal control was assessed with the Wijma Delivery Expectancy/Experience Questionnaire and Pearlin and Schooler's mastery scale. A hierarchical linear analysis was performed. Results Satisfaction with childbirth benefited most consistently from the fulfilment of expectations. In addition, the experience of personal control buffered the lowering impact of labour pain. Women with high self-efficacy showed more satisfaction with self-, midwife- and physician-related aspects of the birth experience. Conclusion Our findings focus the attention toward personal control, self-efficacy and expectations about childbirth. This study confirms the multidimensionality of childbirth satisfaction and demonstrates that different factors predict the various dimensions of satisfaction. The model applies to both Belgian and Dutch women. Cross-national comparative research should further assess the dependence of the determinants of childbirth satisfaction on the organisation of maternity care.